2009
DOI: 10.1007/s10658-009-9512-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Ralstonia solanacearum strains from China

Abstract: A survey of bacterial wilt in China collected 286 strains of Ralstonia solanacearum from 17 plant species in 13 Chinese provinces to investigate genetic diversity using the biovar (bv.) and phylotype classification schemes. A phylotype-specific multiplex-PCR showed that 198 isolates belonged to phylotype I (bv. 3, 4 and 5) and 68 to phylotype II (bv. 2 and bv. 1). A phylogenetic analysis examined the partial sequence of the egl and hrpB gene of all strains and the genetic diversity of 95 representatives was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 24 publications
10
96
0
5
Order By: Relevance
“…The phylotype identity of each strain was determined by multiplex PCR as described by Fegan and Prior (2005). Pmx-PCR was carried out in 25 μl of reaction mixture containing 1× Taq MasterMix (PCR buffer, 1.5 mM MgCl 2 , 250 μM of each dNTP, 50 mM KCl, 10 mM Tris-HCl and 1.25 U of Taq DNA polymerase) (Tiangen Biotech), 6 pmoles of primers Nmult:21:1F, Nmult:21:2F, Nmult:22:InF, 18 pmoles of the primer Nmult:23:AF and 4 pmoles of primers 759 and 760 (all primers are listed in Supplemental Table 2) (Opina et al 1997;Xu et al 2009). This P m x -P C R a m p l i f i e s a 2 8 1 -b p Bu n i v e r s a lR .…”
Section: Dna Assay and Phylotype Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylotype identity of each strain was determined by multiplex PCR as described by Fegan and Prior (2005). Pmx-PCR was carried out in 25 μl of reaction mixture containing 1× Taq MasterMix (PCR buffer, 1.5 mM MgCl 2 , 250 μM of each dNTP, 50 mM KCl, 10 mM Tris-HCl and 1.25 U of Taq DNA polymerase) (Tiangen Biotech), 6 pmoles of primers Nmult:21:1F, Nmult:21:2F, Nmult:22:InF, 18 pmoles of the primer Nmult:23:AF and 4 pmoles of primers 759 and 760 (all primers are listed in Supplemental Table 2) (Opina et al 1997;Xu et al 2009). This P m x -P C R a m p l i f i e s a 2 8 1 -b p Bu n i v e r s a lR .…”
Section: Dna Assay and Phylotype Identificationmentioning
confidence: 99%
“…solanacearum specific reference band in addition to the following phylotype-specific PCR products: a 144-bp band from phylotype I strains; a 372-bp band from phylotype II strains; a 91-bp amplicon from phylotype III strains; and a 213-bp band from phylotype IV strains. The PCR program was carried out in a thermocycler as previously described (Xu et al 2009). Then, 5 μl of PCR product was subjected to electrophoresis on 1.5 % agarose gel, stained with ethidium bromide and visualized on a UV-transilluminator.…”
Section: Dna Assay and Phylotype Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, genes or QTLs associated with BW-resistance were reported against non-characterized R. solanacearum strains, whereas strain-and phylotype-specific QTLs were reported for tomato. Among solanaceous-infecting R. solanacearum populations, phylotype I strains are the most prevalent clade found in most Asian eggplant production areas (Horita and Tsuchiya 2001;Ivey et al 2007;Jaunet and Wang 1999;Xu et al 2009) as well as in Africa (Mahbou Somo Toukam et al 2009), America (Ji et al 2007;Norman et al 2009;Sanchez Perez et al 2008), and the Caribbean ). In a previous study, we showed that phylotype I strains display different virulence patterns, called pathoprofiles, on a core collection of tomato, pepper and eggplant representative of the genetic diversity for resistance in these species (Lebeau et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Classification into phylotypes is done by PCR Multiplex with the Nmult series primers (based on ITS region) and the classification into sequevar by partially sequencing gene egl (encoding the enzyme endoglucanase). Presently, four phylotypes and 51 sequevares of R. solanacearum are described (XU et al, 2009;FONSECA et al, 2014). Analysis of genetic diversity can be conducted based on repetitive sequences (rep-PCR), comprised by the elements BOX, ERIC, and REP, by randomly amplified DNA (RAPD), by amplification of restriction fragments (AFLP), repeated simple sequences (SSR) and by polymorphisms based on restriction fragment size (RFLP) (JAUNET;WANG, 1999;VANDEWALLE;LUISETTI, 1999;COENYE;VANDAMME, 2003;YU et al, 2003;KUMAR;SARMA;ANANDARAJ, 2004;SILVEIRA et al, 2005;LOPES, 2007;IVEY et al, 2007).…”
Section: Genetic Diversity Of Ralstonia Solanacearum In Brazilmentioning
confidence: 99%